Seminar Motivasi : Membangun Karakter Positif Gen Alfa Untuk Meraih Impian - Siskawati, Isna (STAI Publisistik Thawalib Jakarta, 2024)
The aim of motivational seminars is to build positive character and provide enthusiasm and encouragement to students in achieving their goals and dreams. The service was carried out face to face with a duration of 4 (four) hours at the Mts Rahmania Islamic School, South Tangerang. Participants are students in grades 7, 8 and 9 who are currently referred to as Gen Alfa. The methods used are lectures, discussions and practice individually and in groups. Practices include saying positive words and positive characters, making self-quotes and writing down dreams and aspirations. The equipment used includes: stationery, laptop, LCD projector, microphone and sound system. The seminar material consists of 4 (four) themes; build your positive character, achieve your dreams, you are great and life is beautiful. Service results: the seminar ran satisfactorily based on the results of the impression sheet and messages written by participants and parents.